The Authenticity and Authority of Islam - Womack, Deanna Ferree (2015)
This paper examines the concept of Islamic authority in relation to early twentieth-century Protestant missionary writings on Islam and Muhammad Rashid Rida’s commentaries on mission publications in his Cairo-based journal, al-Manar. While Rida’s Salafi reformism has been the subject of much discussion, scholars have given little attention to the content of the missionary writings Rida engaged. Treatments of Rida’s work have also neglected to address the vision of Islamic authority that emerges from his responses to Christian polemics. This paper gives both subjects further consideration as it discusses Protestant missionary approaches to Islam, examines Rida’s writings on Christianity, and assesses his response to a widely circulated article on Islam by Temple Gairdner, a prominent British missionary with the Church Missionary Society in Egypt.
Keywords: Rashid Rida -- Protestant missions -- Islam -- Temple Gairdner -- Egypt; Rashid Rida -- missions protestantes -- islam -- Temple Gairdner -- Egypte